Electron-ion mixed conductor sulfide solid electrolyte material and preparation method and application thereof
By coating the two-dimensional transition metal layered material MXene on the sulfide solid electrolyte and through ball milling and calcining treatment, the stability and space charge layer problems of sulfide electrolyte in the air are solved, achieving high conductivity and long Battery performance for life.
Patent Information
- Application Number
- CN202411595903.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
AI Technical Summary
The stability of sulfide electrolytes in the air is poor, resulting in a decrease in ionic conductivity and a problem with space charge layer, which affects the rate performance and service life of the battery.
The two-dimensional transition metal layered material MXene is used as the surface cladding layer, and the air stability and electron and ion conductivity of the sulfide solid electrolyte are improved by ball milling and calcining.
It significantly improves the air stability and conductivity of the sulfide electrolyte, enhances the rate performance and service life of the battery, and reduces production costs.
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electron-ion mixed conductor sulfide solid electrolyte material and a preparation method and application thereof. Background Art
[0002] With the increasing rise of new energy materials, lithium-ion batteries have rapidly occupied the battery market for electric vehicles and electronic products with their high energy density and high cycle efficiency, becoming the most widely used commercial secondary battery. As the most important part of lithium batteries, electrolytes have always been the focus of attention. In recent years, with the continuous improvement of people's requirements for battery performance, solid electrolytes have developed rapidly due to their high performance advantages and will be commercialized in the near future. Among them, sulfide solid electrolytes are expected by the industry because of their high ionic conductivity and good electrochemical stability.
[0003] However, one of the main drawbacks that sulfide electrolytes need to overcome is their poor stability in air. The PS bonds of sulfide electrolytes will hydrolyze under the action of water molecules in the air to generate toxic H 2 S gas, and the electrolyte structure will collapse during the hydrolysis process, causing the ionic conductivity to drop sharply. At present, the main method of surface coating is to effectively improve the air stability of sulfide electrolyte materials. The mainstream coating materials are polymer coating and oxide coating. However, although these two coating materials can improve the air stability of sulfide electrolyte materials, the ionic conductivity of the coating materials is low, which makes the ionic conductivity of the coated sulfide electrolyte materials decrease by an order of magnitude compared with the uncoated sulfide electrolyte materials.
[0004] In addition, the chemical potential difference between the sulfide electrolyte and the positive electrode material will lead to the appearance of a charge layer. The existence of the chemical potential difference causes the lithium ions to move from the sulfide solid electrolyte side to the oxide positive electrode material side, and the positive electrode and the electrolyte simultaneously form a space charge layer. However, the lower electronic conductivity of the sulfide solid electrolyte layer causes the charge layer on the positive electrode side to disappear, and the chemical potential of the lithium ions on the electrolyte side must continue to move toward the positive electrode to reach equilibrium, and the space charge layer continues to be generated, forming a very large resistance. In order to solve the problem of the space charge layer of the sulfide electrolyte material, the electronic conductivity of the sulfide solid electrolyte layer can be increased, thereby suppressing the existence of the space charge layer.
[0005] In order to solve the above-mentioned problems of air stability and space charge layer, it is crucial to select a suitable coating material. The two-dimensional material MXene has good air stability and high electronic conductivity, and can be used as a coating material for sulfide solid electrolytes, which is expected to solve the above-mentioned problems. Summary of the invention
[0006] The purpose of the present application is to provide an electron-ion mixed conductor sulfide solid electrolyte material and its preparation method and application. The sulfide solid electrolyte material has good air stability and high electronic and ionic conductivity, which can effectively improve the rate performance of the battery and extend the service life of the battery. There is no need to prepare the battery cell in a dew point room at -60°C, thereby reducing production costs.
[0007] In a first aspect, the present application provides a method for preparing an electron-ion mixed conductor sulfide electrolyte material, which is characterized by comprising: using a sulfide solid electrolyte as a core, coating a two-dimensional transition metal layered material MXene as a surface coating layer on the surface of the core, and obtaining the electron-ion mixed conductor sulfide electrolyte material by ball milling and calcination.
[0008] In the embodiment, the sulfide solid electrolyte has a high ionic conductivity, which can approach or even exceed the level of liquid electrolyte, which is crucial for achieving fast charging and discharging and high power output. Using sulfide solid electrolyte as the core helps to reduce the weight and volume of the battery, thereby increasing the energy density of the battery.
[0009] Furthermore, in order to improve the air stability of the sulfide solid electrolyte and ensure high electronic and ionic conductivity, the present application uses a two-dimensional transition metal layered material MXene as a surface coating layer to coat the sulfide solid electrolyte. Since the two-dimensional transition metal layered material MXene has high electronic conductivity, and the layered structure of MXene can provide a channel for rapid transmission of ions, it is beneficial to the transmission of ions in the sulfide solid electrolyte and improves the ionic conductivity of the sulfide solid electrolyte.
[0010] At the same time, the two-dimensional transition metal layered material MXene has good mechanical properties and can be used as a flexible electrolyte coating layer to adapt to sulfide solid electrolyte materials of different shapes and sizes. It can also effectively isolate the direct contact between the sulfide solid electrolyte and the electrode material, and form a good interface contact with a variety of electrode materials, which helps to improve the interface compatibility between the sulfide solid electrolyte and the electrode, reduce interfacial side reactions, and improve the stability of the sulfide solid electrolyte and the electrode, thereby improving the safety performance of the battery.
[0011] Furthermore, since the structural characteristics of the two-dimensional transition metal layered material MXene are that a large number of metal ions and terminated hydroxyl or fluoride groups are exposed on the surface, its surface energy is relatively high and its oxygen resistance in the air is relatively poor. When the two-dimensional transition metal layered material MXene is used as a surface coating, the metal ions on its surface may act as electron donors or acceptors or undergo charge transfer with adsorbed molecules or electrode materials, affecting the electronic properties of MXene such as the electronic state and electron mobility. Even uneven distribution or defects of metal ions may cause electron scattering, thereby affecting the electron transmission efficiency.
[0012] In the present application, the composite material obtained by coating the sulfide solid electrolyte with the two-dimensional transition metal layered material MXene is calcined to combine the S in the sulfide solid electrolyte with the metal ions in the MXene to form a stable sulfide coating, thereby improving the oxidation resistance of the MXene in the air and improving its chemical stability during the charge and discharge process.
[0013] In some embodiments, the sulfide solid electrolyte includes at least an argyrodite-type electrolyte, a Li 2 S-SiS 2 , Li 2 S-SiS 2 , Li 3 PS 4 , Li 10 G 2 S 12 , Li 4 S N 4 ·LiI, Li 7 P 3 S 11 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 4 S N 4 , Li 3.8 Sn 0.8 As 0.2 S 4 , Li 4 Sn 0.9 Si 0.1 S 4 , Li 10 SnP 2 S 12 , Li 7 GePS 8 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 3.25 P0.95 S 4 , Li 11 Si 2 PS 12 , Li 7 P 2 S 8 I. 80(0.7Li 2 S·0.3P 2 S 5 )·20LiI、95(0.8Li 2 S·0.2P 2 S 5 )·5LiI、Li 3.85 Sn 0.85 Sb 0.15 S 4 、75Li 2 S·21P 2 S 5 ·4P 2 O 5 、33(0.7B 2 S 3 0.3P 2 S 5 )·67Li 2 S, 67(0.75Li 2 S·0.25P 2 S 5 )·33LiBH 4 、70Li 2 S·29P 2 S 5 1P 2 O 5 One of them.
[0014] In some embodiments, the general formula of the two-dimensional transition metal layered material MXene is M n+1 AX n (n=1-4), wherein M is selected from one of the transition metals of Group 18B-VIB, A is selected from one of the elements of Group IIIA or Group IVA, and X is carbon or nitrogen.
[0015] In some embodiments, the calcination temperature is 100-500° C., and the calcination time is 1-10 h.
[0016] In some embodiments, the calcination temperature is 300-500° C., and the calcination time is 2-5 hours.
[0017] In the embodiment, when the calcination temperature reaches 100°C, the sulfur in the sulfide solid electrolyte reacts with the functional groups on the surface of MXene to form thio compounds or sulfided MXene. When the calcination temperature is increased to 200°C, the reaction of sulfur in the sulfide solid electrolyte with MXene is more complete, and sulfide of MXene can be formed and some oxygen-containing groups between MXene layers begin to be removed, increasing the interlayer distance, thereby improving the conductivity of the material. Further, when the calcination temperature is increased to 300-500°C, the sulfur in the sulfide solid electrolyte reacts with MXene completely, the oxygen content in the MXene material is further reduced, a more stable sulfide structure is formed, the MXene layer structure is partially reconstructed or shrunk, and the conductivity and air stability of the material are further improved.
[0018] Therefore, in the embodiment, the calcination temperature is controlled to be 100-500° C., and a suitable calcination time is selected according to the calcination temperature to ensure that the sulfur in the sulfide solid electrolyte and the MXene are completely sulfurized.
[0019] In some embodiments, the method specifically includes the following steps: S1, weighing a sulfide solid electrolyte and a two-dimensional transition metal layered material MXene according to a proportion and then ball milling them to obtain material 1; S2, ball milling material 1 for a second time to obtain material 2; S3, calcining material 2 to obtain the electron-ion mixed conductor sulfide electrolyte material.
[0020] In some embodiments, the mass ratio of the sulfide solid electrolyte to the two-dimensional transition metal layered material MXene is 100:(1-10).
[0021] In some embodiments, the mass ratio of the sulfide solid electrolyte to the two-dimensional transition metal layered material MXene is 100:(3-8).
[0022] In the embodiment, the mass ratio of the sulfide solid electrolyte and the two-dimensional transition metal layered material MXene needs to be controlled to ensure sufficient reaction of the subsequent sulfide solid electrolyte and the two-dimensional transition metal layered material MXene.
[0023] In some embodiments, the ball milling in S1 is performed by a planetary ball mill, the size of the zirconia balls is 8-15 mm, the linear speed is 15-25 m / min, and the grinding time is 20-60 min.
[0024] In some embodiments, the ball milling in S2 is performed by a planetary ball mill, the size of the zirconia balls is 1-3 mm, the linear speed is 20-30 m / min, and the grinding time is 20-60 min.
[0025] In the embodiment, by repeatedly ball milling with zirconia balls of different sizes, the particle size of the sulfide electrolyte and the two-dimensional transition metal layered material MXene is effectively reduced, the specific surface area is increased and the two are mixed evenly, the interface contact between MXene and the sulfide electrolyte is improved, the interface interaction is enhanced, and the mechanical force generated during the ball milling process can activate the surface of MXene and increase surface defects, which is beneficial to the subsequent calcination reaction of the two and is beneficial to improving the overall performance of the prepared electron-ion mixed conductor sulfide solid electrolyte material.
[0026] In a second aspect, the present application provides an electron-ion mixed conductor sulfide electrolyte material, characterized in that the electron-ion mixed conductor sulfide electrolyte material is prepared by the preparation method described in any one of the first aspects.
[0027] In a third aspect, the present application provides an all-solid-state battery, characterized in that the all-solid-state battery includes a positive electrode layer, and the positive electrode layer includes the electron-ion conductor sulfide solid electrolyte material described in the second aspect.
[0028] The electron-ion conductor sulfide solid electrolyte material and the preparation method thereof provided in this application include but are not limited to the following: The surface of the electron-ion conductor sulfide solid electrolyte material of the present application is coated with a MXene material, which has a lamellar structure and has good air stability. After coating, the presence of a waxy solid organic compound therein enables the electrolyte to have good air stability, eliminating the need to prepare the battery cell in an ultra-low dew point environment, thereby reducing production costs.
[0029] The electron-ion conductor sulfide solid electrolyte material of the present application has a surface coating material MXene with rich functional groups, which can react with sulfur ions in the electrolyte, so that the coating layer material and the core have good stability, and have good stability with both without producing side reactions.
[0030] The electron-ion conductor sulfide solid electrolyte material of the present application has good ionic conductivity and electronic conductivity due to the coating material MXene, and the sulfide solid electrolyte has a high electronic conductivity that can inhibit the appearance of a space charge layer, thereby improving the electronic conductivity of the positive electrode, which is beneficial to increasing the rate of the battery cell and reducing the content of conductive carbon. It has high ionic conductivity and can maintain the intrinsic ionic conductivity of the sulfide electrolyte to the greatest extent. DETAILED DESCRIPTION
[0031] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.
[0032] The present application provides a method for preparing an electron-ion mixed conductor sulfide electrolyte material, which is characterized by comprising: using a sulfide solid electrolyte as a core, coating a two-dimensional transition metal layered material MXene as a surface coating layer on the surface of the core, and obtaining the electron-ion mixed conductor sulfide electrolyte material by ball milling and calcining.
[0033] The present application uses a two-dimensional transition metal layered material MXene as a surface coating layer to coat a sulfide solid electrolyte, thereby improving the air stability of the sulfide solid electrolyte and ensuring high electronic and ionic conductivity, and utilizing the high electronic conductivity of the two-dimensional transition metal layered material MXene to improve the ionic conductivity of the sulfide solid electrolyte. Furthermore, the composite material prepared by coating the sulfide solid electrolyte with the two-dimensional transition metal layered material MXene is calcined to combine the S in the sulfide solid electrolyte with the metal ions in the MXene to form a stable sulfide coating, thereby improving the oxidation resistance of the MXene in the air and improving its chemical stability during the charge and discharge process.
[0034] The electronic-ion mixed conductor sulfide electrolyte material provided in the present application and its preparation method and application will be described in detail below in conjunction with specific embodiments.
[0035] The present application provides a method for preparing an electron-ion mixed conductor sulfide electrolyte material, which is characterized by comprising: using a sulfide solid electrolyte as a core, coating a two-dimensional transition metal layered material MXene as a surface coating layer on the surface of the core, and obtaining the electron-ion mixed conductor sulfide electrolyte material by ball milling and calcining.
[0036] In some embodiments, the sulfide solid electrolyte includes at least an argyrodite-type electrolyte, a Li 2 S-SiS 2 , Li 2 S-SiS 2 , Li 3 PS 4 , Li 10 G 2 S 12 , Li 4 S N4 ·LiI、Li 7 P 3 S 11 、Li 9.54 Yes 1.74 P 1.44 S 11.7 Cl 0.3 、Li 4 SnS 4 、Li 3.8 Sn 0.8 As 0.2 S 4 、Li 4 Sn 0.9 Yes 0.1 S 4 、Li 10 SnP 2 S 12 、Li 7 GePS 8 、Li 3.25 Ge 0.25 P 0.75 S 4 、Li 3.25 P 0.95 S 4 、Li 11 Yes 2 P.S. 12 、Li 7 P 2 S 8 I、80(0.7Li 2 S·0.3P 2 S 5 )·20LiI、95(0.8Li 2 S·0.2P 2 S 5 )·5LiI、Li 3.85 Sn 0.85 Sb 0.15 S 4 、75Li 2 S·21P 2 S 5 ·4P 2 About 5 、33(0.7B 2 S 3 ·0.3P 2 S 5 )·67Li 2 S、67(0.75Li 2 S·0.25P 2 S 5 )·33LiBH 4 、70Li2 S·29P 2 S 5 1P 2 O 5 One of them.
[0037] In the embodiments, the above-mentioned sulfide solid electrolyte basically has high ionic conductivity, good interface compatibility and relatively low processing temperature, and is suitable for being combined as a core with the two-dimensional transition metal layered material MXene to prepare an electron-ion mixed conductor sulfide solid electrolyte material.
[0038] In some embodiments, the general formula of the two-dimensional transition metal layered material MXene is M n+1 AX n (n=1-4), wherein M is selected from one of the transition metals of Group 18B-VIB, A is selected from one of the elements of Group IIIA or Group IVA, and X is carbon or nitrogen.
[0039] In some embodiments, the calcination temperature is 100-500°C, for example, 100°C, 200°C, 300°C, 400°C or 500°C, and the calcination time is 1-10h, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.
[0040] In some embodiments, the method specifically includes the following steps: S1, weighing a sulfide solid electrolyte and a two-dimensional transition metal layered material MXene according to a proportion and then ball milling them to obtain material 1; S2, ball milling material 1 for a second time to obtain material 2; S3, calcining material 2 to obtain the electron-ion mixed conductor sulfide electrolyte material.
[0041] In some embodiments, the mass ratio of the sulfide solid electrolyte to the two-dimensional transition metal layered material MXene is 100:(1-10), for example, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10.
[0042] In the embodiment, the mass ratio of the sulfide solid electrolyte and the two-dimensional transition metal layered material MXene needs to be controlled to ensure sufficient reaction of the subsequent sulfide solid electrolyte and the two-dimensional transition metal layered material MXene.
[0043] In some embodiments, the ball milling in S1 is performed using a planetary ball mill, the zirconia ball size is 8-15 mm, for example, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm, the linear speed is 15-25 m / min, and the grinding time is 20-60 min.
[0044] In some embodiments, the ball milling in S2 is performed by a planetary ball mill, the size of the zirconia balls is 1-3 mm, 1 mm, 2 mm or 3 mm, the linear speed is 20-30 m / min, and the grinding time is 20-60 min.
[0045] In the embodiment, by repeatedly ball milling with zirconia balls of different sizes, the particle size of the sulfide electrolyte and the two-dimensional transition metal layered material MXene is effectively reduced, the specific surface area is increased and the two are mixed evenly, the interface contact between MXene and the sulfide electrolyte is improved, the interface interaction is enhanced, and the mechanical force generated during the ball milling process can activate the surface of MXene and increase surface defects, which is beneficial to the subsequent calcination reaction of the two and is beneficial to improving the overall performance of the prepared electron-ion mixed conductor sulfide solid electrolyte material. Example
[0046] This embodiment provides an electron-ion mixed conductor sulfide electrolyte material, which is composed of a core and a two-dimensional transition metal layered material MXene coated on the surface of the core; wherein the core is a sulfide solid electrolyte and the solid electrolyte is a sulfur-silver-germanium mineral structure Li 6 PS 5 Cl, coating layer is Ti 2 C.
[0047] The specific preparation process of the sulfide electrolyte material of this embodiment is as follows: S1, sulfide solid electrolyte Li 6 PS 5 Cl and Ti 2 C was weighed at a mass ratio of 100:3 and then ball milled. The zirconia ball size was 10 mm, the linear speed was 20 m / min, and the grinding time was 30 min to obtain material 1.
[0048] S2. Material 1 is subjected to secondary ball milling, with a zirconia ball size of 2 mm, a linear speed of 25 m / min, and a grinding time of 30 min to obtain material 2.
[0049] S3, sintering material 2 at a sintering temperature of 300° C. for 2 h, and obtaining an electrolyte material after cooling.
[0050] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor, which is composed of a core and a two-dimensional carbon material coated on the surface of the core; wherein the core is a sulfide solid electrolyte with a sulfur-silver-germanium mineral structure Li 6 PS 5 Cl, the coating layer is graphene.
[0051] The specific preparation process of the sulfide solid electrolyte material of this embodiment is as follows: S1, sulfide solid electrolyte Li 6 PS 5 Cl and graphene were weighed in a mass ratio of 100:3 and then ball-milled. The zirconia ball size was 10 mm, the linear speed was 20 m / min, and the grinding time was 30 min to obtain material 1.
[0052] S2. Material 1 is subjected to secondary ball milling, with a zirconia ball size of 2 mm, a linear speed of 25 m / min, and a grinding time of 30 min to obtain material 2.
[0053] S3, sintering material 2 at a sintering temperature of 300° C. for 2 h, and then cooling to obtain an electrolyte material.
[0054] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 only uses glycerol stearate to coat the inner core, and other raw materials, amounts and preparation methods are the same as those of Example 1.
[0055] This embodiment provides a sulfide solid electrolyte material with high air stability, which is composed of a core and a polymer coated on the surface of the core; wherein the core is a sulfide solid electrolyte with a sulfur silver germanium mineral structure Li 6 PS 5 Cl, the coating layer is glyceryl stearate.
[0056] The specific preparation process of the sulfide solid electrolyte material of this embodiment is as follows: S1, sulfide electrolyte Li 6 PS 5 Cl and glycerol stearate were weighed in a mass ratio of 100:3 and then ball-milled. The zirconia ball size was 10 mm, the linear speed was 20 m / min, and the grinding time was 30 min to obtain material 1.
[0057] S2. Material 1 is subjected to secondary ball milling, with a zirconia ball size of 2 mm, a linear speed of 25 m / min, and a grinding time of 30 min to obtain material 2.
[0058] S3. Sintering material 2 at a sintering temperature of 100°C (polymer materials cannot be subjected to high temperature heat treatment) for 2 hours, and obtaining the electrolyte material after cooling.
[0059] The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 only uses lithium aluminum titanium phosphate to coat the inner core, and other raw materials, amounts and preparation methods are the same as those in Example 1. Example
[0060] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor, in which the coating material is replaced with Ti 3 C 2 , the remaining steps are the same as those in Example 1. Example
[0061] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor. The sulfide solid electrolyte replaces Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , the remaining steps are the same as those in Example 1. Example
[0062] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor, in which the mass ratio of the core material to the coating material is replaced with 100:8, and the remaining steps are the same as those in Embodiment 1. Example
[0063] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor. The size of the zirconium oxide balls in S1 is adjusted to 12 mm, the ball milling speed is adjusted to 15 m / min, the grinding time is 20 min, and the remaining steps are the same as in Example 1. Example
[0064] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor. The size of the zirconia balls in S2 is adjusted to 3 mm, the ball milling speed is adjusted to 30 m / min, the grinding time is 50 min, and the remaining steps are the same as in Embodiment 1. Example
[0065] This embodiment provides a sulfide solid electrolyte material of an electron-ion mixed conductor. The calcination temperature is adjusted to 500° C., the calcination time is 5 h, and the remaining steps are the same as those in Embodiment 1.
[0066] 1. Test samples: 2. Test items: 2.1 Air stability test: Spread more than 2g of the test sample in a 500mL beaker and place it in a closed space with dry air at a dew point of -45℃ for a period of time, and measure the ionic conductivity of each sample before and after placement.
[0067] 2.2 Ionic conductivity test: Each sample was pressed into a sheet-like sulfide solid electrolyte material with a diameter of 10 mm and a thickness of 1 mm under the conditions of a water content of less than 10 ppm and a pressure of 200 MPa. Then, an electrochemical impedance spectroscopy (EIS) test was performed at room temperature of 25°C with carbon as the blocking electrode to calculate the ionic conductivity.
[0068] 2.3 Electronic conductivity test: The sample for measuring ionic conductivity was used for electronic conductivity test, and the test method was DC polarization method. The DC polarization voltage was 1.0 V, the application time was 1800 s, and the DC polarization test was carried out at room temperature 25°C. The polarization voltage was read and the electronic conductivity was calculated.
[0069] 2.4 Cycle test of all-solid-state batteries: The assembly method of the all-solid-state battery is as follows: positive electrode NCM811, surface loading 5mAh / cm 2 , N / P ratio is 1.1, the positive electrode content in the positive electrode is 80wt%, the electrolyte uses the electrolyte material in each embodiment and comparative example, the content is 15wt%, the electrolyte layer thickness is 100μm, and the electrolyte material is not coated with Li 6 PS 5 Cl, the negative electrode uses a carbon nano-coated negative electrode. (The control group is a sulfide electrolyte Li without any modification 6 PS 5 Cl) The cycle test method is as follows: the charge and discharge voltage is 3.0-4.25V, the cycle temperature is 60℃, the first cycle is 0.05C, and the second cycle is set according to different rate requirements. The evaluation of the battery's rate performance is based on the discharge specific capacity.
[0070] The results of the above tests are shown in Table 1.
[0071] Table 1 sample Ionic conductivity (mS / cm) Electronic conductivity (S / cm) Ionic conductivity after 4 hours in drying room (mS / cm) <![CDATA[1C discharge specific capacity / mAh•g -1 > <![CDATA[3C discharge specific capacity / mAh•g -1 > <![CDATA[5C discharge specific capacity / mAh•g -1 > Example 1 3.87 <![CDATA[5×10 -3 ]]> 3.24 192.0 173.3 150.0 Comparative Example 1 1.63 <![CDATA[4.6×10 -3 ]]> 1.21 184.4 160.2 83.0 Comparative Example 2 0.54 <![CDATA[2.9×10 -10 ]]> 0.52 127.3 90.9 Short Circuit Example 2 3.93 <![CDATA[8.2×10 -3 ]]> 3.6 190.0 175.2 148.5 Example 3 8.97 <![CDATA[6.0×10 -3 ]]> 8.10 191.2 173.5 149.6 Example 4 3.2 <![CDATA[2.4×10 -2 ]]> 3.0 189.1 176.1 155.2 Example 5 3.85 <![CDATA[8.2×10 -3 ]]> 3.20 193.0 169.3 148.0 Example 6 3.74 <![CDATA[6.1×10 -3 ]]> 3.24 190.3 170.3 145.8 Example 7 3.66 <![CDATA[8.0×10 -3 ]]> 3.14 192.8 172.2 150.0 Control group 4.13 <![CDATA[6.5×10 -8 ]]> 2.23 182.3 133.1 Short Circuit From the test data in Table 1, it can be seen that the sulfide electrolyte Li 6 PS 5 The air stability test of Cl was poor, and the ion conductivity decreased by 46% after being placed in a drying room for 4 hours, while the air stability of the electrolyte materials in Examples 1-7 was good, and the decrease was less than 20%. The 1C, 3C, and 5C discharge specific capacities of the electrolyte materials in Examples 1-7 were all improved to varying degrees, indicating that the prepared battery had good rate performance and high cycle stability.
[0072] In Comparative Examples 1 and 2, the electronic conductivity of the electrolyte materials prepared by using non-MXene materials such as glycerol stearate and lithium aluminum titanium phosphate as coating materials could not be stably improved compared with the control group, and even the electronic conductivity of the electrolyte material in Comparative Example 2 was significantly reduced. The electronic conductivity of the electrolyte materials prepared in Examples 1-7 was greatly improved, which was about 77,000 to 120,000 times that of the control group.
[0073] The electron-ion conductor sulfide solid electrolyte material and the preparation method thereof provided in this application include but are not limited to the following: The surface of the electron-ion conductor sulfide solid electrolyte material of the present application is coated with a MXene material, which has a lamellar structure and has good air stability. After coating, the presence of a waxy solid organic compound therein enables the electrolyte to have good air stability, eliminating the need to prepare the battery cell in an ultra-low dew point environment, thereby reducing production costs.
[0074] The electron-ion conductor sulfide solid electrolyte material of the present application has a surface coating material MXene with rich functional groups, which can react with sulfur ions in the electrolyte, so that the coating layer material and the core have good stability, and have good stability with both without producing side reactions.
[0075] The electron-ion conductor sulfide solid electrolyte material of the present application has good ionic conductivity and electronic conductivity due to the coating material MXene, and the sulfide solid electrolyte has a high electronic conductivity that can inhibit the appearance of a space charge layer, thereby improving the electronic conductivity of the positive electrode, which is beneficial to increasing the rate of the battery cell and reducing the content of conductive carbon. It has high ionic conductivity and can maintain the intrinsic ionic conductivity of the sulfide electrolyte to the greatest extent.
[0076] In summary, after reading the contents of this application, those skilled in the art will appreciate that the aforementioned application contents may be presented only in an exemplary manner and may not be restrictive. Although not explicitly stated herein, those skilled in the art will appreciate that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are within the spirit and scope of the exemplary embodiments of this application.
Claims
1. A method for preparing an electron-ion mixed conductor sulfide electrolyte material, characterized in that: include: A sulfide solid electrolyte is used as the inner core, and a two-dimensional transition metal layered material MXene is coated on the inner core surface as a surface coating layer. The electron-ion mixed conductor sulfide electrolyte material is obtained by ball milling and calcination.
2. The preparation method according to claim 1, characterized in that: The sulfide solid electrolyte includes at least argyrodite-type electrolyte, Li2S-SiS2, Li2S-SiS2, Li3PS4, Li 10 GeP2S 12 、Li4SnS4·LiI、Li7P3S 11 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 、Li4SnS4、Li 3.8 Sn 0.8 As 0.2 S4、Li4Sn 0.9 Si 0.1 S4, Li 10 SnP2S 12 、Li7GePS8、Li 3.25 Ge 0.25 P 0.75 S4, Li 3.25 P 0.95 S4, Li 11 Si2PS 12 , Li7P2S8I, 80(0.7Li2S·0.3P2S5)·20LiI, 95(0.8Li2S·0.2P2S5)·5LiI, Li 3.85 Sn 0.85 Sb 0.15 One of S4, 75Li2S·21P2S5·4P2O5, 33(0.7B2S3·0.3P2S5)·67Li2S, 67(0.75Li2S·0.25P2S5)·33LiBH4, 70Li2S·29P2S5·1P2O5.
3. The preparation method according to claim 1, characterized in that: The general formula of the two-dimensional transition metal layered material MXene is M n+1 AX n (n=1-4), wherein M is selected from one of the transition metals of Group 18B-VIB, A is selected from one of the elements of Group IIIA or Group IVA, and X is carbon or nitrogen.
4. The preparation method according to claim 1, characterized in that: The calcination temperature is 100-500° C., and the calcination time is 1-10 hours.
5. The preparation method according to claim 1, characterized in that: The specific steps include: S1, weighing a sulfide solid electrolyte and a two-dimensional transition metal layered material MXene according to a proportion and then ball milling them to obtain material 1; S2, ball milling material 1 for a second time to obtain material 2; S3, calcining material 2 to obtain the electron-ion mixed conductor sulfide electrolyte material.
6. The preparation method according to claim 1, characterized in that: By weight, the mass ratio of the sulfide solid electrolyte to the two-dimensional transition metal layered material MXene is 100:(1-10).
7. The preparation method according to claim 1, characterized in that: The S1 is ball milled by a planetary ball mill, the size of the zirconium oxide balls is 8-15 mm, the linear speed is 15-25 m / min, and the grinding time is 20-60 min.
8. The preparation method according to claim 1, characterized in that: The S2 is ball milled by a planetary ball mill, the size of the zirconium oxide balls is 1-3 mm, the linear speed is 20-30 m / min, and the grinding time is 20-60 min.
9. An electron-ion mixed conductor sulfide electrolyte material, characterized in that: The electron-ion mixed conductor sulfide electrolyte material is prepared by the preparation method according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: The all-solid-state battery comprises a positive electrode layer, wherein the positive electrode layer comprises the electron-ion conductor sulfide solid electrolyte material according to claim 9.
Citation Information
Cited By
High-crystallinity ion-electron mixed conductor material and application
CN121331830A
High-crystallinity ion-electron mixed conductor material and applications
CN121331830B
Composite solid electrolyte material and preparation method and application thereof
CN122532369A